ANALISIS PENGANGKATAN KEPALA OTORITA IBU KOTA NUSANTARA OLEH PRESIDEN TERHADAP PASAL 18 AYAT 4 UNDANG-UNDANG DASAR 1945 DALAM PERSPEKTIF HUKUM TATA NEGARA - ARDANITA, RAHAYU; Artina, Dessy; Zulhidayat, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The constitutionality in Indonesia is measured based on its alignment with the 1945Constitution. The examination of the role and appointment of the Chief of Authority in theSpecial Capital Region of the National Capital is essential to comprehend its governancemechanism. The Chief of Authority of the Indonesian Capital City is directly appointed by thePresident and serves a five-year term, which, however, does not conform to the general electionmechanism stipulated in Article 18 Clause 4 of the 1945 Constitution used by other regionalleaders.The type of research utilized in this study is normative legal research. In collecting data fornormative research, a literature review method (library research) was employed. This researchalso employs qualitative data analysis and generates descriptive data.From the research findings and discussions conducted, several conclusions are derived:firstly, the appointment of the Chief of Authority of the Indonesian Capital City by the Presidentpotentially violates the principle of regional autonomy regarding the direct appointment andplacement of the Chief of Authority by the President. This violation threatens the autonomy andauthority of regions, which contradicts the principle of decentralization mandated by Article 18Clause 4 of the 1945 Constitution. Secondly, the ideal concept of appointing the Chief ofAuthority of the Indonesian Capital City by the President aims to balance power between thecentral government and regional governments by maintaining the concept of checks andbalances and regional autonomy. The concepts of checks and balances and regional autonomyare considered crucial to prevent power abuse.The recommendations include proposing a judicial review of Article 4 Clause 1 letter b,Article 5 Clause 4, Article 9, Article 10, Article 13 Clauses (1) and (2) of the Law on theIndonesian Capital City, as well as on the division of authority between the central governmentand regions in the context of the Indonesian Capital City Authority in Article 10 of PresidentialRegulation Number 62 regarding the Indonesian Capital City Authority to ensure alignment withthe principles of regional autonomy stipulated in Article 18 Clause 4 of the 1945 Constitution.Additionally, the restoration of the role of the Regional People's Representative Council (DPRD)in the governance structure of the Indonesian Capital City Authority as the representation of thepeople in accordance with the provisions of Article 18 Clause 3 of the 1945 Constitution isrecommended. Furthermore, inclusive dialogue and active participation from all stakeholders,including the central government, regional governments, civil society, and other democraticinstitutions, in formulating policies related to the appointment of the Chief of Authority.Keywords: Chief of Authority, Indonesian Capital City, Regional Autonomy